La fête et le spectacle carnavalesques dans Le Mât de cocagne (1979) et Hadriana dans tous mes rêves (1988) de René Depestre - Alvarez Domenech, Irene (Il Tolomeo, 2018)
The aim of this article is to bring together two of René Despestre’s novels, Le Mât de cocagne (1979) and Hadriana dans tous mes rêves (1988), and place them within the tradition of the carnivalesque as it was discussed by Mikhail Bakhtin in L’œuvre de François Rabelais et la culture populaire au Moyen Âge et sous la Renaissance. By taking into account this wider perspective, I intend to show that the presence of a diegetic spectacle reinforces the subversive value of the two works by including a moment of utopian relief that invites both the characters and the readers to engage in a fight for freedom.